Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru di MTs Miftahul Jannah Segedong - Hasanuddin; Samiyah (CV Putra Publisher, 2024)
This study aims to examine the role of principal leadership in improving teacher pedagogical competence at MTs Miftahul Jannah Segedong. Improving the quality of education through teacher competency development is the main focus, considering the challenges of declining quality of education at various levels. Using a qualitative approach, this study explores the leadership strategies implemented by principals to support the development of teacher pedagogical competence. Data were collected through in-depth interviews, participant observation, and document analysis. The main findings of the study indicate that strategies such as conducting periodic workshops, ongoing teacher training, providing motivation through awards, intensive supervision, and holding regular school meetings are very effective in improving the quality of learning in the school. In addition, the principal plays a role in creating a school culture that supports collaboration and pedagogical innovation among teachers. The implications of this study highlight the importance of the role of the principal in fostering a conducive and sustainable learning environment for teacher professional development, which ultimately has a positive impact on the quality of education. Recommendations for this study include increasing policy support for teacher competency development and strengthening school leadership capacity.